Proposing a Theoretical Framework of the Successful Factors of Microenterprises in Indonesia - Hawariyuni, Weni; Gadar, Kamisan (International Journal of Engineering and Technology, 2018)
The objective of this paper is to suggest a theoretical framework of the factors determine the success of microenterprise. This study concentrates on borrowers of BRI Unit in Medan, Indonesia. BRI (Bank Rakyat Indonesia/People's Bank of Indonesia) is recognized as one of government banks with the excellent reputation in Indonesia. World Bank stated that BRI as the first commercial microfinance in this world [1]. BRI has many branches in all of the provinces in Indonesia. BRI Unit is part of BRI. This unit is focusing on providing microcredit products. It targets microenterprises and small vendors as its principal borrowers. BRI Unit provides its primary micro product called KUPEDES (Kredit Umum Pedesaan/General Rural Credit). The government of Indonesia also appointed BRI Unit to distribute its subsidized micro product called KUR (Kredit Usaha Rakyat/People Business Credit). This study is believed to provide a theoretical framework which may be useful for Indonesian government and BRI Unit, mainly to expand the microenterprise performing in Indonesia, including in Medan.